English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Equation: (cosθ + sinθ) / (sinθ)

I'm not sure what (cosθ + sinθ) or (cos^2θ * sin^2θ) equal to. I know sin^2θ + cos^2θ = 1 but I don't use that identity do I, since in the problem, cos and sin aren't squared. Thanks for the help.

2007-03-17 04:05:51 · 5 answers · asked by shih rips 6 in Science & Mathematics Mathematics

Equation: (cosθ + sinθ) / (sinθ)

How do I simplify this expression?

2007-03-17 04:22:34 · update #1

5 answers

You could try dividing it out:
= cot(x) +1
Multiply by (cot(x)-1)/(cot(x)-1)
= (cot^2(x) -1)/(cot(x)-1)
= csc^2(x)/(cot(x)-1)
There isn't really an ultimate simplification for this one.
cos^2(x)*sin^2(x) = (1/4)sin^2(x)
by the identity that (sin(x)*cos(x)) = (1/2)sin(2x)

2007-03-17 04:17:58 · answer #1 · answered by J Z 4 · 0 0

I apologize for my confusion; what's the identity equation?
I notice you're lacking an equal sign hence my confusion.

2007-03-17 04:19:50 · answer #2 · answered by Puggy 7 · 0 0

to make certain an id, you will possibly be able to desire to instruct that the two aspects are equivalent. and you are trying this via manipulating one among the two aspects of the expression or the two. regrettably, there at the instant are not any policies in doing that. you will possibly be able to desire to try this via trial and mistake. in this subject, control the spectacular edge of the expression such that: [(sin?+cos?) / sin?] - [(cos?-sin?) / cos?] = (a million/cos?)(a million/sin?) Then multiply the two aspects of the expression via (cos?)(sin?), so as that cos?(sin? + cos?) - sin?(cos? - sin?) = a million increasing it provides cos^2 ? + cos?sin? - sin?cos? + sin^2 ? = a million cos^2 ? + sin^2 ? = a million a million = a million

2016-10-18 22:13:54 · answer #3 · answered by porix 4 · 0 0

(cosθ + sinθ) / (sinθ)= cot(theta)+1 because:

tan (theta) = sin(theta)/cos(theta)
cot (theta) = 1/tan(theta)
?=(cos(theta)+sin (theta))/sin(theta)
?= cos(theta)/sin(theta) + sin(theta)/sin(theta)
?=cot(theta)+1
therefore, (cosθ + sinθ) / (sinθ)= cot(theta)+1

2007-03-17 04:26:13 · answer #4 · answered by Anonymous · 0 0

=cotan theta +1 = (1+tan theta)/tan theta

2007-03-17 04:12:17 · answer #5 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers